Evidence on the Accuracy of Merger Simulations - Weinberg, Matthew C.; Hosken, Daniel (The Review of Economics and Statistics, 2013)
Abstract This paper evaluates the efficacy of a structural model of oligopoly used for merger review. Using premerger data, we estimate several demand systems and use a static Bertrand model to simulate the price effects of two mergers. Using pre- and postmerger data, we directly estimate the price effects. The direct estimates imply that one merger resulted in moderate price increases, while the second left prices essentially unchanged. While some simulations are similar to the directly estimated price effects, overall simulations overstate the price effects in one case and understate them in the other. Explanations for the discrepancies are explored.